2019
DOI: 10.1136/bmjopen-2018-026140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of real-time visual feedback device ‘Quality Cardiopulmonary Resuscitation (QCPR) Classroom’ with a metronome sound on layperson CPR training in Japan: a cluster randomized control trial

Abstract: Objectives‘Quality Cardiopulmonary Resuscitation (QCPR) Classroom’ was recently introduced to provide higher-quality Cardiopulmonary Resuscitation (CPR) training. This study aimed to examine whether novel QCPR Classroom training can lead to higher chest-compression quality than standard CPR training.DesignA cluster randomised controlled trial was conducted to compare standard CPR training (control) and QCPR Classroom (intervention).SettingLayperson CPR training in Japan.ParticipantsSix hundred forty-two people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…As in this study, QCPR Classroom participants could see their CPR results on a large screen, while the control group only received subjective instructor feedback. QCPR Classroom was found to help students obtain high-quality CPR training, especially on correct compression depth and full recoil [35]. Other research studying the in uence of received feedback on CPR quality [36][37] have reported similar conclusions.…”
Section: Discussionmentioning
confidence: 61%
“…As in this study, QCPR Classroom participants could see their CPR results on a large screen, while the control group only received subjective instructor feedback. QCPR Classroom was found to help students obtain high-quality CPR training, especially on correct compression depth and full recoil [35]. Other research studying the in uence of received feedback on CPR quality [36][37] have reported similar conclusions.…”
Section: Discussionmentioning
confidence: 61%
“…Following removal of 196 duplicates, 681 sources were screened via titles and abstracts, resulting in 201 possible relevant studies. Upon full text analysis, 32 studies met inclusion criteria and were included in our review including 14 randomised controlled trials (RCTs) [14,17,18,20,23,24,29,32,33,38,40,42,44,45], 08 randomised trials (RTs) [25][26][27][28]31,36,37,41] and 10 randomised cross-over trials (RCOTs) [15,16,19,21,22,30,34,35,39,46]. The flow chart of the search and selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The use of ARTF devices has been examined in each study included in this review and it has been demonstrated that all feedback and/or prompt devices may not have the same impact on performance. Generally, CPR training utilising ARTF results in improved acquisition of CPR skills, longer retention and subsequent enhanced performance when compared to baseline or control groups [16][17][18][19]20,23,32,39,44,45]. Metrics such as chest compression rate, chest compression depth, recoil, handoff time, fatigue reduction and general quality of CPR, significantly improved as a result of the use of ARTF during training in those studies.…”
Section: Analysis Of Individual Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Tanaka et al observed similar findings that the visual and audible feedback improves the quality of CPR. 19 In the real-world situations, the use of feedback devices like a metronome for rate and CPR meter for depth would be helpful to ensure high-quality CPR.…”
Section: Discussionmentioning
confidence: 99%